“It’s complicated:” the continuity and correlates of cycling in cohabiting and marital relationships - Vennum, Amber V.; Lindstrom, Rachel; Monk, J. Kale; Adams, Rebekah (My University, 2014)
Given previous research on the risks associated with cycling in young adult dating relationships, the present study examines the frequency with which cyclical dating relationships (relationships that end and renew) persist into cohabitation and marriage, the characteristics of these relationships, and the constraints associated with cycling during these stages using a nationally representative sample of cohabiting (n = 323) and married (n = 752) couples. Using retrospective accounts, results suggest that over one-third of cohabiters and one-fifth of spouses have experienced a breakup and renewal in their current relationship. Additionally, partners who have experienced cycling are at greater risk for further cycling and experiencing greater constraints to permanently ending the relationship, greater uncertainty in their relationship’s future, and lower satisfaction.
Keywords: Cohabitation; Churning; Marital satisfaction; Relationship cycling; Structural constraints